Randomised controlled trial of three day versus 10 day intravenous antibiotics in acute pyelonephritis: effect on renal scarring. Issue 3 (1st March 2001) - Benador, D; Neuhaus, T J; Papazyan, J-P; Willi, U V; Engel-Bicik, I; Nadal, D; Slosman, D; Mermillod, B; Girardin, E
Abstract : BACKGROUND: Acute pyelonephritis often leaves children with permanent renal scarring. AIMS: To compare the prevalence of scarring following initial treatment with antibiotics administered intravenously for 10 or three days. METHODS: In a prospective two centre trial, 220 patients aged 3 months to 16 years with positive urine culture and acute renal lesions on initial DMSA scintigraphy, were randomly assigned to receive intravenous ceftriaxone (50 mg/kg once daily) for 10 or three days, followed by oral cefixime (4 mg/kg twice daily) to complete a 15 day course. After three months, scintigraphy was repeated in order to diagnose renal scars. RESULTS: Renal scarring developed in 33% of the 110 children in the 10 day intravenous group and 36% of the 110 children in the three day group. Children older than 1 year had more renal scarring than infants (42% (54/129) and 24% (22/91), respectively). After adjustment for age, sex, duration of fever before treatment, degree of inflammation, presence of vesicoureteric reflux, and the patients' recruitment centres, there was no significant difference between the two treatments on renal scarring. During follow up, 15 children had recurrence of urinary infection with no significant difference between the two treatment groups. CONCLUSION: In children with acute pyelonephritis, initial intravenous treatment for 10 days, compared with three days, does not significantly reduce the development of renal scarring.